Konsep Filsafat Pendidikan Islam dalam Pengembangan Kurikulum Islam - Mardinal Tarigan; Balqis Qonita Harahap (Universitas Dehasen Bengkulu, 2022)
The philosophy of Islamic education as a result of ideas with a distinctive Islamic pattern, is essentially a concept of thinking about education that is based on Islamic teachings. The whole thought process is based on deep and broad experiences about life's problems and realities in the universe and oneself. The purpose of this study is to explain the foundation of Islamic education in the perspective of Islamic education philosophy. The method in this study uses a qualitative method with the type of descriptive analytic research. The result of this research is that the philosophy of Islamic education can help educational designers and people who need it to form the right thinking towards the educational process. Besides, the philosophy of education can help determine the goals and functions of education and improve the quality of education, evaluation, guidance and counseling. This is in accordance with the objectives of the philosophy of Islamic education which is essentially identical to the goals of Islamic teachings. Both come from the same source, namely the Qur'an and al-Hadith.